2022
DOI: 10.3390/cryst12010087
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Different Types of Honey and Propolis Collected from Romanian Accredited Beekeepers and Consumer’s Risk Assessment

Abstract: Honey is a natural product recognized and appreciated for its nutritional value and therapeutic potential. However, the quality of bee honey is essential because various contaminants can seriously affect consumers’ health. In the experimental part of the work, we analyzed different types of honey (linden, black locust, rapeseed and multifloral honey) and propolis, which were collected from Romanian accredited beekeepers who placed beehives in two areas characterized by different industrial activity: area 1 (A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
(50 reference statements)
1
18
1
Order By: Relevance
“…Our results are in accordance with findings of other studies conducted in order to assess potential human risks associated with mussel consumption in the region of Black Sea [54][55][56]. It should be noted also that calculated hazard quotients for investigated heavy metals within the current research were higher than values found in other investigated food categories in Romania (honey, food supplements) [57,58].…”
Section: Estimated Risk Through Mussel Consumptionsupporting
confidence: 91%
“…Our results are in accordance with findings of other studies conducted in order to assess potential human risks associated with mussel consumption in the region of Black Sea [54][55][56]. It should be noted also that calculated hazard quotients for investigated heavy metals within the current research were higher than values found in other investigated food categories in Romania (honey, food supplements) [57,58].…”
Section: Estimated Risk Through Mussel Consumptionsupporting
confidence: 91%
“…Honey, due to its high nutritional value and numerous health-promoting properties, is a valuable component of the daily diet. The chemical composition of honey is varied and depends mainly on the region where it is produced, the soil conditions, and the water and air quality, which affect the quality of the food sources for bees, including the presence and level of chemical pollutants [ 1 ]. The health risks associated with honey consumption stem from the presence of pesticide residues (including active substances and their metabolites), antibacterial substances (including antibiotics), and heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Although our data showed that heavy metal levels in honey were relatively low compared to the food limits set by the Codex Alimentarius Commission (FAO/WHO), the Malaysian Food Regulations 1985, and the Agency for Toxic Substances and Disease Registry (ATSDR), there was a trend of elevated As, Cd, Cr, and Pb levels in Sipitang, Papar, and Kimanis, which are all located near major roads, cities, petrochemical hub, and power plants (Tables 1 and 2 ). The studies on the honey of Romanian honey bee showed that elevated levels of heavy metals were found in some of the samples from industrial areas and Cd and Pb exceeded the maximum permissible levels in some samples [ 36 ]. A recent study in Lithuania indicated that the concentration of heavy metals (Cd, Cr, Cu, Pb, and Ni) in honey samples were found to significantly decrease with increasing distance from potential pollution sources [ 7 ].…”
Section: Resultsmentioning
confidence: 99%